The psychology of prejudice : from attitudes to social action - Jackson, Lynne M. (American Psychological Association, 2020)
"Given the weaponization of cultural and ideological differences in politics, education, and social media today, the need to understand and fight prejudice is urgent. This second edition of Lynne Jackson's seminal text presents a significantly updated review of the psychological underpinnings of prejudicial thoughts and behaviors. Jackson synthesizes new research from various areas of psychology to analyze contemporary examples of prejudice, including anti-immigrant policies, police violence against minorities, anti-woman and LGBTQ backlash, and ageist cultural biases. She also explores frequently overlooked issues related to prejudice, such as environmental inequality and speciesism. Drawing from literature in evolutionary, developmental, social, and personality psychology, Jackson explores the biological and environmental roots of prejudice, including how people develop essentialist views in childhood and learn to favor ingroup members and dehumanize outgroup members. She draws connections between these beliefs and other social justice issues showing how they give rise to greater social problems like inequality and political polarization. She also offers readers a blueprint for overcoming these deeply embedded biases by improving intergroup attitudes and building communities to create progressive social change"--